Effects of creep diet complexity on individual consumption characteristics and growth performance of neonatal and weanling pigs - Sulabo, R.C.; Bergstrom, J.R.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
In Exp. 1, 96 sows (PIC C29) and their litters were used to determine the effects of creep diet complexity on preweaning performance and the proportion of piglets consuming creep feed. The experimental treatments were: (1) no creep feed (n = 26), (2) simple creep diet (n = 26), and (3) complex creep diet (n = 44). Pigs fed the complex creep diet had greater (P < 0.03) ADG and tended to have greater (P < 0.06) total gain than pigs fed the simple creep diet, with no creep pigs intermediate. Litters fed the complex creep diet consumed twice the total (2.73 vs. 1.37 lb; P < 0.0006) and daily (0.91 vs. 0.45 lb; P < 0.0006) creep feed intake of litters fed the simple creep diet. The high-complexity creep diet improved (P < 0.0001) the proportion of eaters from 28% to 68%. A greater (P < 0.10) proportion of eaters were nursing in the middle and posterior teats (57% and 52%, respectively) than in the anterior teats (38%). In Exp. 2, 675 pigs from Exp. 1 (initial BW 14.1 lb and 21.2 ± 0.2 d) were used to determine whether social facilitation occurs between eaters and non-eaters in commercial nursery groups. The treatments were: non-eater group (pigs that were not provided any creep feed or non-eaters of creep feed), eater group (pigs that positively consumed creep feed), and mix group (pigs that were 51% non-eaters and 49% eaters). Each treatment had 25 pigs per pen and 9 replications (pens). In the initial 3 d postweaning, eaters had greater (P < 0.01) ADG and (P < 0.002) ADFI than non-eaters, with the mix group being intermediate. Overall ADG of the eater group was 6.2% higher (P < 0.05) than that of the non-eater group. For social facilitation to occur, weight gains of non-eaters in the mix pens should be either (1) closer to the weight gains of eaters in the mix pen or (2) greater than the weight gains of the non-eater group. Results showed that non-eaters within the mix pens failed both criteria. In conclusion, the high-complexity creep diet improved preweaning ADG, litter creep feed intake, and the proportion of eaters. Eaters had improved postweaning feed intake, daily gains, and weight uniformity and reduced postweaning lag. Mixing eaters with non-eaters within pens in large commercial groups did not stimulate feed intake and daily gains of non-eaters, which indicates that social facilitation did not occur.
Keywords: Swine; Behavior; Creep feeding; Diet complexity